Survival at Stalag IVB : soldiers and airmen remember Germany's largest POW camp of World War II - Vercoe, Tony, 1919- (McFarland, 2006)
"This first-person historical document recalls day-to-day life in Stalag IVB, beginning with technical details such as the background and layout of Germany's largest POW camp. The work is based on the firsthand experiences of the author and contributions from other veterans of the camp"--Provided by publisher.